Urgensi dan Penerapan Konsep Cyber Notary di Masa Pandemi Covid-19 - Siti Malikhatun Badriyah; Intan Nur Baiti (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractCyber Notary concept is alternative that can be used Notary to work and making transactions during the pandemic. Article 15 paragraph (3)UUJN provides opportunities application of Cyber Notary concept where Notary can use functions and authority based on technology, such as making deeds and conducting certification by electronic. The purpose of this study is to analyze and describe reasons Cyber Notary concept cannot be applied in Covd-19 pandemic situation and the opportunities implementng Cyber Notary concept related to Notary's authorty in Notary Regulations. The method used is normative legal research by conducting legal analysis based on study from legislation and literature of Cyber Notary. It was concluded that the factor meaning of